2000
DOI: 10.1161/01.cir.102.20.2479
|View full text |Cite
|
Sign up to set email alerts
|

Improved Vascular Endothelial Function After Oral B Vitamins

Abstract: Background-Hyperhomocysteinemia is an independent risk factor for coronary heart disease (CHD). Dietary supplementation with B vitamins lowers plasma homocysteine by up to 30%. However, little is known about the potential beneficial effects of homocysteine lowering on vascular function in patients with CHD. Methods and Results-We investigated 89 men with CHD (aged 56 [range 39 to 67] years). Brachial artery flow-mediated dilatation (endothelium dependent) and nitroglycerin-induced dilatation (endothelium indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(52 citation statements)
references
References 43 publications
2
45
3
2
Order By: Relevance
“…While previous studies have suggested that the benefits of folic acid on FMD are partly dependent on its homocysteine-lowering effect, 7,8 our present study suggests the effects are independent of homocysteine-lowering, confirming the findings of the other recent diabetic studies. 25,26 It has been realized that the oxidative stress of diabetes may lead to oxidation of tetrahydrobiopterin, an essential co-factor of eNOS, resulting in the uncoupling of the eNOS enzyme and a loss of NO availability.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While previous studies have suggested that the benefits of folic acid on FMD are partly dependent on its homocysteine-lowering effect, 7,8 our present study suggests the effects are independent of homocysteine-lowering, confirming the findings of the other recent diabetic studies. 25,26 It has been realized that the oxidative stress of diabetes may lead to oxidation of tetrahydrobiopterin, an essential co-factor of eNOS, resulting in the uncoupling of the eNOS enzyme and a loss of NO availability.…”
Section: Discussionsupporting
confidence: 92%
“…Our FMD results demonstrate considerable inter-patient variation of FMD with a wide range of values noted with folic acid and placebo, which is similar to that seen in other studies which have used similar methodology. 7,8,21,23,25,[28][29][30] Despite this variability, our study was sufficiently powered to demonstrate the absolute 2.6% increase in FMD with as few as 18 patients in this cross-over design. 31,32 On the other hand, as our study was only powered according to the effect on FMD, this small sample size may have been insufficient to demonstrate a significant secondary effect on the inflammatory markers.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Nyolc héttel később megmérték a résztvevők teljes, a fehérjéhez kötött és a plazma homociszteinszintjeit, amelyek szignifikánsan csökkentek. Mindemellett javult a vizsgált egyének ereinek endothelfunkciója is [31].…”
Section: B 12 -Vitamin Folsav éS Vasunclassified